Associations of the BDNF Val66Met Polymorphism With Body Composition, Cardiometabolic Risk Factors, and Energy Intake in Youth With Obesity: Findings From the HEARTY Study - Goldfield, Gary S.; Walsh, Jeremy; Sigal, Ronald J.; Kenny, Glen P.; Hadjiyannakis, Stasia; De Lisio, Michael; Ngu, Mathew; Prud’homme, Denis; Alberga, Angela S.; Doucette, Steve; Goldfield, Diana B.; Cameron, Jameason D. (Frontiers in Neuroscience, 2021)
Background: The brain-derived neurotrophic factor (BDNF) Val66Met polymorphism is functionally related to BDNF, and is associated with obesity and metabolic complications in adults, but limited research exists among adolescents. Purpose: To examine carriers and non-carriers of the BDNF Val66Met polymorphism on body composition, energy intake, and cardiometabolic profile among adolescents with obesity. Methods: The sample consisted of 187 adolescents with obesity; 99 were carriers of the homozygous Val (G/G alleles) and 88 were carriers of the hypofunctioning heterozygous Val/Met (G/A) or Met (A/A) alleles. Cardiometabolic profile and DNA were quantified from fasted blood samples. Body composition was assessed by magnetic resonance imaging (MRI). Results: Compared to carriers of the homozygous Val (G/G) allele, carriers of the Val/Met (G/A) or Met/Met (A/A) variants exhibited significantly higher protein (p=0.01) and fat (p=0.05) intake, C-Reactive protein (p=0.05), and a trend toward higher overall energy intake (p=0.07), fat-free mass (p=0.07), and lower HDL-C (p=0.07). Conclusions: Results showed for the first time that among youth with obesity, carriers of the Val66met BDNF Met-alleles exhibited significantly higher C-reactive protein and energy intake in the form of fat and protein compared to Val-allele carriers, thereby providing support for the possible role of BDNF in appetite, weight, and metabolic regulation during adolescence.